Az Európai Unió foglalkoztatáspolitikája - Molnár Emese (Acta Universitatis Szegediensis : acta juridica et politica : publicationes doctorandorum juridicorum, 2001)
Unemployment is a big problem in the European Union and all the world over. The Treaty of Amsterdam approved at the European Council meeting in June 1997, has a new Employment Title. In this Treaty employment is considered for the first time as a common concern in the European Union. According to the Treaty of Amsterdam a number of quantifiable targets must be introduced to which the Member States will commit themselves to achieve trough both individual and concerted action. These targets are the so-called Employment Policy Guidelines. The Member States should incorporate the Employment Policy Guidelines into the national action plans and report to the Commission on their implementation. The guidelines are adopted by the Council on a proposal from the Commission. They define four main strategic priorities (pillers) to concentrate on: employability, enterpreneurship, adaptability and equal opportunities. Employability is the people's capacity to be employed. The first of the four pillars focuses on this and on tackling the skills gap. Skill development and lifelong learning are the key objectives. The particular emphasis in this part of the Guidelines on ensuring that young people and the unemployed (particulary long-term unemployed) are equipped to take advantage of new employment opportunities in the fast-changing labour-market. The Member States should encourage the transition from passive measures to active measures, they should review their benefit and tax system and easy the transition from scool to work. The last point in the piller of employability is promoting a labour market open to all. The second of the Guidelines'four pillers derives from recognition that the creation of more and better jobs requires a dinamic and entreprising climate. The developmentt of new enterprises, and the growth of small and medium-sized enterprises is essential for job creation and for the expansion of training opportunities for young people. There is a need for greater adaptability on the part of businesses, but also on the part of workforce. The third piller focuses on the adaptability of enerprises and workers to changing technology and markets. It recognises that a balance must be stuck between the need of businesses for flexibility, and the needs of employees for security and employability. The fourth piller is about the equal opportunities for women and men. Women still have particular problems in gaining access to the employment market. For women is very difficult reconciling work and family life. There must be an adequate provision of good quality care for children in order to support women's and men's entry and continued participation in the labour market. Those returning to the labour market after an absence may have outmoded skills and experience difficulty gaining access to training. The Member States must gradually eliminate the obstacle of such return.